Am I allowed to sell myself and my child? - Gottlieb, Ann Cathrine; Lyngsø, Maria Nørgaard (Politica, 2019)
Danish legislation seeks to discourage people from becoming prostitutes and surrogate mothers. However, prostitution and surrogacy do not differ in morally relevant respects from comparable professions or practices not restricted by the law. Accordingly, a less restrictive legislation pertaining to prostitution and surrogacy is warranted. A positive side effect of this is to reduce the stigmatization that seems to affect practitioners of both professions.